Face validity : exploring the relationship between facial affect recognition and psychopathic traits with high-risk prisoners in New Zealand : a thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University - Tamatea, Armon James (Massey University, 2011)
Psychopathy, as a psychiatric entity, psychological construct, and social idea has suffered from conceptual vagueness and misuse for over two centuries. Currently, psychopathic individuals are considered to present as having a constellation of affective, interpersonal, and behavioural characteristics that typically incurs great social, economic, and human costs by virtue of repeated displays of extreme antisocial behaviour. As such, individuals who are considered ‘psychopathic’ tend to be over-represented in judicial and correctional settings, tend to re-offend faster and more often than nonpsychopathic offenders, and are also resistant to conventional treatment efforts – so much so, in fact, as to have the reputation of being ‘untreatable’. Historical and current conceptualisations of psychopathy have emphasised moral, behavioural, cognitive, neurocognitive, and even physiological differences. However, the various social and interpersonal contexts in which these individuals interact and indeed offend do not appear to have been fully explored in the literature. This study explored social cognitive aspects of violent offenders with psychopathic traits with a view towards informing intervention approaches with this high-risk and potentially dangerous group. Furthermore, the impact of psychopathy is largely evident in the social realm and suggests differences in social information-processing. The role of emotions, especially those of others, is an important construct across theories of social interactions and impairments in affective processing, such as low empathy, guilt, and fear that are common features of psychopathy. Given that recognising emotions from facial cues is an early developmental marker ofemotional and social development, it presents as an interface between behaviour and social cognitive processes. This study sought to investigate the basic relationships between psychopathy and social cognitive phenomena. Male prisoners (N = 68) from New Zealand prisons were invited to (1) identify facial expressions from Ekman and Friesen’s (1976) Pictures Of Facial Affect stimuli set; (2) discriminate emotions from displayed pairs of faces; and (3) repeat the tasks after being administered a frustrating task. It was hypothesised that men who presented with psychopathic traits (as measured on the Psychopathic Personality Inventory-Revised; PPI-R; Lilienfeld & Widows, 2005) would reveal biased responding before and after the stress intervention. Contrary to expectations, the findings from this study did not – on the whole – support the hypothesis. However, the outcomes called into question the supposedly pervasive and apparently cognitively-impaired nature of psychopathic social information-processing.
Keywords: Psychopaths; Face perception; Facial expression; Emotion